ZnO Thin Film Flexible UV Photodetectors: Regulation on the ZnO/Au Interface by Piezo‐Phototronic Effect and Performance Outcomes. Issue 16 (13th June 2019) - Duan, Yuhan; Cong, Mingyu; Jiang, Dayong; Zhang, Wei; Yang, Xiaojiang; Shan, Chuncai; Zhou, Xuan; li, Meng; Li, Qian
Abstract: The ZnO flexible ultraviolet photodetectors (UV PDs) with poly(ethylene terephthalate) (PET) substrate are manufactured successfully at room temperature, and the effect of strain on PDs performance are studied. When subjected to 0.2 tensile stress, the responsivity of PDs is increased by 20% and sensitivity is increased by 770%. This is due to the influence of piezo‐phototronic effect on the transport behavior of photogenerated carriers at the interface of ZnO/Au Schottky junction. The polarization charge generated by the piezoelectric element breaks the original thermodynamic equilibrium. As a consequence, the charge at the interface is being redistributed, and the Schottky barrier height (SBH) and depletion layer width change, thus regulating the interface characteristics. This effect has value for the optimization and regulation of the UV PDs performance. Furthermore, current study proves that the piezo‐phototronic effect not only exists in ZnO nanomaterials, but also has a significant piezo‐phototronic effect on high‐quality thin film ZnO materials. In addition, this study also provides an extension field for flexible UV PDs based on piezo‐phototronic effect of semiconductor materials. Abstract : The ZnO thin film flexible ultraviolet photodetectors (UV PDs) with poly(ethylene terephthalate) (PET) substrate are used to research the regulation on the ZnO/Au interface by piezo‐phototronic effect. The polarization charge generated by strain causing the charge at the interface is redistributed, and the Schottky barrier height (SBH) and depletion layer width change, thus regulating the interface characteristics.